Purwarupa Mesin Penukar Sampah Botol Menjadi Poin Berbasis IoT - Iswanto Iswanto; Samsul Budiarto (Jurnal Media Informatika, 2025)
This research aims to design and build a prototype of a bottle waste exchange machine into points based on the Internet of Things (IoT). The city of Bandung faces serious problems related to waste management, especially plastic bottle waste. Similar conditions occur in the Nurtanio University Bandung environment, low student awareness of the importance of environmentally friendly waste management worsens this situation. The prototype of the bottle waste exchange machine into points is expected to provide a solution by automating the process of waste identification, sorting and collection. This machine prototype uses a NodeMCU ESP8266 microcontroller as a control center. Inductive and capacitive proximity sensors are used to detect waste types. The IoT system allows real-time monitoring and management of the machine through a mobile application. In testing, the machine successfully identified plastic bottles, glass and cans with a high level of accuracy. The implementation of this Smart Recycling Machine is also equipped with a user-friendly web interface and mobile application, making it easier for users to operate and monitor exchange transactions. Data obtained from these sensors is sent to the server via a Wi-Fi network, then processed and displayed in the form of information that is easy for users to understand. In addition, this machine is also able to provide periodic reports on the amount and type of waste that has been exchanged by users, which can be used for further analysis purposes. The results of the study indicate that the use of IoT technology in waste management can increase the efficiency of the recycling process and provide ease of monitoring. It is hoped that the implementation of this machine can increase student awareness of the importance of good waste management and support environmental conservation efforts in the Nurtanio University Bandung environment.